The Relationship between Personality Traits of Dayakese Students and Their Strategies in Learning Arabic as a Foreign Language - Wahdah, Nurul; Ainin, Moh.; Hamid, M. Abdul (IAIN Samarinda, 2018)
This study aims at finding out the relationship between personality traits and Arabic Language Learning Strategies (LLS) for the Dayakese learners of Islamic Senior High School Tumbang Samba, Central Kalimantan, Indonesia. Eighty one students were asked to participate in this study. The instruments used were the Big Five Personality Inventory (BFI) proposed by John (1990) and the Strategy Inventory for Language Learning (SILL) proposed by Oxford (1990). In analysing data, arithmetic mean, standard deviation and correlation coefficient of Pearson were used. The findings can be explained as follows. 1) The agreeableness and conscientiousness traits of Dayakese learners were at moderate levels, and the extroversion, neuroticism and openness to experience traits of them were at high levels. The most preferred personality trait was openness to experience. 2) The language learning strategies used by students on the six strategies were at different levels. The cognitive, compensation, affective and social strategies were at low levels. The memory and metacognitive strategies were at moderate levels. The most popularly strategy used was metacognitive strategies and the least strategy used was cognitive strategies. 3) Although there is not a statistically significant correlation between Dayakese learners ‘personality and Arabic language learning strategies generally, the significant correlations were found between neuroticism trait and memory, metacognitive, and social strategies; and between openness to experience trait and cognitive, compensation, metacognitive, affective and social strategies specifically.